E- Business para la oferta de bienes del sector secundario de la provincia de Cotopaxi. - Suárez Cruz, Diego Armando (2020)
This degree work proposes a B2B type business model directed towards companies in the secondary economic sector of Cotopaxi province with the aim of integrating new characteristics and properties within the existing electronic commerce processes in the market and in turn to develop approaches towards creating a new value proposition for companies and end consumers. The proposed offer for the aforementioned business plan incorporates a set of services that revolve around the use of off-line and on-line use tools that allow companies to efficiently manage the stock of products and, at the same time, the information of commercial type with the purpose of automating the online sales processes within a Web and App environment, which on the other hand, it connects with the final consumer to deliver a new and simple way to buy online. The financial analysis shows that the business plan is viable since the NPV of $ 26,049.83 is favorable and the IRR corresponds to 23%.